Real-time displacement measurement system using phase-shifted optical pulse interferometry: Application to a seismic observation system. (18th January 2016) - Yoshida, Minoru; Hirayama, Yoshiharu; Takahara, Atsushi; Kashi, Motofumi; Takeuchi, Keiji; Ikeda, Toshiharu; Hirai, Fumio; Mizuno, Yosuke; Nakamura, Kentaro; Kimura, Hitoshi; Ino, Norio; Inoue, Wataru
Abstract: We developed a method of detecting incident light levels on the oscillator surfaces and light pulses that include two interfering pulses with a phase shift of π/2 (phase-shifted optical pulse interferometry). This system enables the measurement of displacements greatly exceeding the half wavelength of the laser. Moreover, it allows measurements at multiple locations with a single optical fiber for using optical pulses. In this study, we conducted an interference experiment using 30 ns optical pulses and transmitted them at 1 µs intervals. We confirmed that the above two measurements are possible. Furthermore, from the data of the oscillator used for verification, we showed that measurements on the order of nanometers are possible. Since this method does not require a power supply to the oscillator, its widespread applications in physical exploration can be expected.